Characteristics of Outpatients with Chronic Tonsillitis at the ENT Clinic of Sanjiwani Regional General Hospital, Gianyar, in 2023–2024 - Mulyawan Made Bramastya Nugraha Teja Kusuma; Widhidewi Ni Wayan; Indraningrat Anak Agung Gede; Santosa Agus (Ganesha Medicina, 2026)
Chronic tonsillitis is a recurrent and persistent inflammation of the palatine tonsils that commonly affects children to young adults and may impact quality of life. This study aimed to describe the characteristics of outpatients with chronic tonsillitis at the ENT Clinic of Sanjiwani Regional General Hospital, Gianyar, during the 2023–2024 period. This study employed a descriptive quantitative design with a retrospective cross-sectional approach using total sampling from 51 medical records. Univariate analysis was performed using Microsoft Excel to evaluate variables including age, sex, clinical symptoms, tonsillar hypertrophy grade (Brodsky classification), and management. The majority of patients were female (58.8%) and aged ≤16 years (45.1%). The most common symptom was halitosis (39.2%), followed by dysphagia and dilated tonsillar crypts (17.6% each). The most frequent tonsillar hypertrophy grade was T2 (25–50%) at 39.2%, which was more common in females and in patients aged ≤16 years. The most frequently administered treatment was medical therapy (60.8%), particularly for mild to moderate grades, whereas surgical referral was more common in cases with more severe tonsillar enlargement. In conclusion, chronic tonsillitis in this outpatient setting predominantly affected young female patients, with halitosis and T2 tonsillar hypertrophy as the main findings. Most cases were managed conservatively, highlighting the need to strengthen clinical guidelines and patient education.